The Incidental Pundit: Who Talks Politics with Whom, and Why?. Issue 1 (16th September 2019) - Minozzi, William; Song, Hyunjin; Lazer, David M. J.; Neblo, Michael A.; Ognyanova, Katherine
Abstract: Informal discussion plays a crucial role in democracy, yet much of its value depends on diversity. We describe two models of political discussion. The purposive model holds that people typically select discussants who are knowledgeable and politically similar to them. The incidental model suggests that people talk politics for mostly idiosyncratic reasons, as by‐products of nonpolitical social processes. To adjudicate between these accounts, we draw on a unique, multisite, panel data set of whole networks, with information about many social relationships, attitudes, and demographics. This evidence permits a stronger foundation for inferences than more common egocentric methods. We find that incidental processes shape discussion networks much more powerfully than purposive ones. Respondents tended to report discussants with whom they share other relationships and characteristics, rather than based on expertise or political similarity, suggesting that stimulating discussion outside of echo chambers may be easier than previously thought.